From the Monster to the Kid Next Door: Transgender Children, Cisgender Parents, and the Management of Difference on TV - Prochuk, Alana (Atlantis)

(untitled) (Mount Saint Vincent University, 2014)
This article explores the recent surge in television representations of transgender children. In particular, it analyzes episodes of The Tyra Show, Anderson, 20/20, Dr. Phil, and The Passionate Eye, arguing that these shows exploit the cultural symbolism of childhood to defuse the political challenge posed by trans subjectivity.